1985
DOI: 10.1037/0022-3514.49.5.1416
|View full text |Cite
|
Sign up to set email alerts
|

Is the startle reaction an emotion?

Abstract: In this study, we examined startle reactions in which the subjects did and did not know when a blank pistol would be fired. In addition, we asked subjects to suppress their startle response and to simulate a startle when there was no gunshot. Detailed measurement of facial muscular actions supported most of the findings reported by Landis and Hunt (1939), but our findings suggested that startle be considered a reflex not an emotion. The findings are considered in terms of current disagreements about exactly wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(88 citation statements)
references
References 22 publications
4
82
1
Order By: Relevance
“…In the one prior test of ethnic differences in suppression (Hagemann et al, 2006), ethnicity failed to moderate suppression effects to an acoustic startle. Our findings extend these results using disgust films, a stimulus that is more clearly emotional than the acoustic startle, which is thought to exist on the boundary between emotion and reflex (Ekman, Friesen, & Simons, 1985). We also extended these findings to measures of blood pressure, which support the pattern of suppression-related increases in cardiovascular activation across members of different ethnic groups.…”
Section: Discussionsupporting
confidence: 76%
“…In the one prior test of ethnic differences in suppression (Hagemann et al, 2006), ethnicity failed to moderate suppression effects to an acoustic startle. Our findings extend these results using disgust films, a stimulus that is more clearly emotional than the acoustic startle, which is thought to exist on the boundary between emotion and reflex (Ekman, Friesen, & Simons, 1985). We also extended these findings to measures of blood pressure, which support the pattern of suppression-related increases in cardiovascular activation across members of different ethnic groups.…”
Section: Discussionsupporting
confidence: 76%
“…The fact that all stimuli evoked this early corrugator response, and that a similar initial response component was detected in earlier studies (e.g., Dimberg & Thunberg, 1998), indicates that this is a general response that does not differentiate between the emotional content of the stimuli, but rather reflects a nonspecific effect of visual stimulation. One plausible interpretation is that it reflects a startle reaction, which typically occurs within 200 ms (e.g., Ekman, Friesen, & Simons, 1985), and which also can be elicited by rather weak stimuli (Blumenthal & Goode, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of reasons. Sometimes, authors reported finding significant results only in subsets of their data (e.g., Anolli & Ciceri, 1997;Burns & Kintz, 1976;Ekman, Friesen & Simons, 1985). Some authors reported significance for multivariate tests that analyzed cues together (e.g., Greene et al, 1985;Heilveil & Muehleman, 1981) or analyses that collapsed across other conditions (e.g., DePaulo, Rosenthal, Green, & Rosenkrantz, 1982).…”
Section: Trouble In the Land Of Toysmentioning
confidence: 99%